ADCP ice draft data from AUV Ran missions during Nathaniel B. Palmer cruise NBP2202 - Wahlgren, Stina; Sjövall, Anders; Stedt, Filip; Symons, Mark; Wåhlin, Anna (University of Gothenburg, 2026)
Acoustic Doppler Current Profiler (ADCP) echo intensity data and maps of ADCP-derived ice draft of the Dotson Ice Shelf, collected by the autonomous underwater vehicle (AUV) Ran (Kongsberg Hugin) during the Nathaniel B. Palmer cruise NBP2202. The AUV was equipped with an upward-looking 45 kHz ADCP (RDI Pinnacle 45) during three seabed-following missions: 02, 03 and 04. A summary of the missions are available from researchdata.se (doi: https://doi.org/10.5878/349w-b176).

The process for deriving ice draft from the ADCP echo intensity data is explained in the following article:

Wahlgren S., Wåhlin, A. & Heywood, K. J (2026). Mapping the ice draft of Dotson Ice Shelf with a long-range ADCP on an autonomous underwater vehicle. Journal of Atmospheric and Oceanic Technology [in review].

Data över ekointensitet från Acoustic Doppler Current Profiler (ADCP) samt kartor över Dotsonisens isdraft (dvs djupet på gränsytan mellan hav och is) baserade på dessa mätningar, insamlade med den autonoma undervattensfarkosten Ran (Kongsberg Hugin) under forskningsexpeditionen NBP2202 med Nathaniel B. Palmer. Ran var utrustad med en uppåtriktad 45 kHz ADCP (RDI Pinnacle 45) under tre bottenföljande uppdrag: 02, 03 och 04. En sammanfattning av uppdragen finns tillgänglig på www.snd.se (doi: https://doi.org/10.5878/349w-b176).

Metoden för att härleda isdraft från ekointensitetsdata beskrivs i följande artikel:

Wahlgren, S., Wåhlin, A. & Heywood, K. J. (2026). Mapping the ice draft of Dotson Ice Shelf with a long-range ADCP on an autonomous underwater vehicle. Journal of Atmospheric and Oceanic Technology [under granskning].
ADCP ice draft data from AUV Ran missions during Nathaniel B. Palmer cruise NBP2202
Keywords: GLACIERS/ICE SHEETS; CRYOSPHERIC INDICATORS; Antarctica; Antarktis; polar region; polarområde; Hydrography; Hydrografi; antarctic regions; ocean-ice interaction; interaktion hav-is; Amundsen Sea; Amundsenhavet; ice shelves; shelfis; autonomous underwater vehicle (AUV); autonom undervattensfarkost (AUV); Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Oceans; Kust och hav